2014: OPQ travels East - Nakamatsu, Javier (2014)
Once again the students of the Peruvian delegation selected by the Peruvian Chemistry Olympiad (OPQ) achieved very good results in the international competitions of 2014: the International Chemistry Olympiad (IChO) in Vietnam and the Iberoamerican Chemistry Olympiad (OIAQ) in Uruguay.